Predisposing factors for pressure injuries in patients admitted to a hospital unit (Research, Society and Development, 2023)
A pressure injury is defined as damage that affects the skin and/or underlying soft tissues, commonly over a bony prominence or related to the use of a medical device or other artifact, such as a combination of pressure and shear. This is a descriptive study with a quantitative and qualitative approach, carried out in a hospital that specializes in traumatological and neurological urgencies and emergencies. Data collection took place in the Adult ICU, from November to January 2020. The population consisted of all patients in the aforementioned sector. No exclusion criteria were adopted. The research received a favorable opinion from the CEP, number 3,507,966. In relation to the sociodemographic profile, it was possible to identify a prevalence of males (84.6%), brown ethnicity (92.3%), single marital status (61.5%), age group over 60 years old (30.7 %), as the reason for hospitalization, traumatological causes prevailed (53.85%), according to pressure injuries, stage 2 predominated (61.55%) and the prevalent anatomical location was in the sacral region (84.62%). When it comes to the application of the scales, according to the Braden Scale, the majority of patients (92.3%) were classified as high risk. And in relation to the Fugulin Scale, 76.9% were classified in relation to the degree of dependence as intensive care. The nursing team plays a fundamental role, as they provide direct assistance to patients, so it is necessary to know the predisposing factors, so that prevention strategies can be planned and guarantee safety and a better quality of care provided.